Structural features of coronavirus SARS-CoV-2 spike protein: targets for vaccination - Sternberg, Ariane; Naujokat, Cord (Life sciences, 2020)
Various human pathogenic viruses employ envelope glycoproteins for host cell receptor recognition and binding, membrane fusion and viral entry. The spike (S) glycoprotein of betacoronavirus SARS-CoV-2 is a homotrimeric class I fusion protein that exists in a metastable conformation for cleavage by host cell proteases furin and TMPRSS2, thereby undergoing substantial structural rearrangement for ACE2 host cell receptor binding and subsequent viral entry by membrane fusion. The S protein is densely decorated with N-linked glycans protruding from the trimer surface that affect S protein folding, processing by host cell proteases and the elicitation of humoral immune response. Deep insight into the sophisticated structure of SARS-CoV-2 S protein may provide a blueprint for vaccination strategies, as reviewed herein.
Gesehen am 11.11.2020